Characteristics of A2B7-type LaYNi-based hydrogen storage alloys modified by partially substituting Ni with Mn. (13th April 2017) - Xiong, Wei; Yan, Huizhong; Wang, Li; Verbetsky, V.; Zhao, Xin; Mitrokhin, S.; Li, Baoquan; Li, Jin; Wang, Yan
Abstract: LaY2 Ni10.5− x Mn x ( x  = 0.0, 0.5, 1.0, 2.0) alloys are prepared by a vacuum induction-quenching process followed by annealing. The structure, as well as the hydriding/dehydriding and charging/discharging characteristics, of the alloys are investigated via X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), pressure-composition isotherms (PCI), and electrochemical measurement. The alloys have multiphase structures mainly composed of Gd2 Co7 -type (3R) and Ce2 Ni7 -type (2H) phases. Partial substitution of Ni by Mn clearly increases the hydrogen storage capacity of the alloys. The x  = 0.5 alloy exhibits a maximum hydrogen storage capacity of 1.40 wt % and a discharge capacity of 392.9 mAh g −1, which are approximately 1.5 and 1.9 times greater than those of the x  = 0.0 alloy, respectively. The high-rate dischargeability (HRD) of the x  = 0.5 alloy is higher than that of the other alloys because of its large hydrogen diffusion coefficient D, which is a controlling factor in the electrochemical kinetic performance of alloy electrodes at high discharge current densities. Although the cyclic stability of the x  = 0.5 alloy is not as high as that of the other alloys, its capacity retention ratio is as high as 56.3% after the 400th cycle. The thermodynamic characteristics of the x  = 0.5 alloy satisfy the requirements of the hydride electrode of metal hydride–nickel (MH–Ni) batteries. Graphical abstract: Highlights: A2 B7 -type LaYNiMn alloy belongs to a system of new hydrogen storage materials. Discharge capacities of x  = 0.5, 1.0 alloys exceed theoretical capacity of LaNi5 alloy. LaYNi alloy can be easily prepared compared with the LaMgNi alloys.